2015
DOI: 10.1097/psy.0000000000000195
|View full text |Cite
|
Sign up to set email alerts
|

Altered Patterns of Heartbeat-Evoked Potentials in Depersonalization/Derealization Disorder

Abstract: These results suggest altered cortical representation of afferent signals originating from the cardiovascular system in patients with DPD, which may be associated with higher sympathetic tone. These findings may reflect difficulties of patients with DPD to attend to their actual bodily experiences.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
42
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 82 publications
3
42
0
Order By: Relevance
“…In line with this result, several studies have reported HEP modulations, not only in right electrodes (Pollatos and Schandry, 2004), but also extended to left (Schandry and Weitkunat, 1990; Gray et al, 2007) and central (Schandry and Weitkunat, 1990; Pollatos and Schandry, 2004; Schulz et al, 2015) topographies. Thus, it would seem that interoception and exteroception imply different neural mechanisms indexing attentional processes at very fast ongoing cycles.…”
Section: Discussionsupporting
confidence: 58%
See 3 more Smart Citations
“…In line with this result, several studies have reported HEP modulations, not only in right electrodes (Pollatos and Schandry, 2004), but also extended to left (Schandry and Weitkunat, 1990; Gray et al, 2007) and central (Schandry and Weitkunat, 1990; Pollatos and Schandry, 2004; Schulz et al, 2015) topographies. Thus, it would seem that interoception and exteroception imply different neural mechanisms indexing attentional processes at very fast ongoing cycles.…”
Section: Discussionsupporting
confidence: 58%
“…Studies on various psychiatric and neurological conditions have shown alterations in this ERP relative to healthy controls (Terhaar et al, 2012; Muller et al, 2015; Schulz et al, 2015; García-Cordero et al, 2016). However, in all of these studies, HEP results emerged from contrasts between samples with resting-state activity (Muller et al, 2015) or a basal interoceptive condition—i.e., none of them examined differences relative to exteroceptive performance.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…From the view that interoception mediates between the perception of somatic states and domains that are highly relevant for successful coping with the challenges of everyday life, such as intuition, emotion and (decision) behaviour, it follows that improved understanding of the underlying functional anatomy may aid understanding and interventions for a wide array of issues including maladaptive response to somatic cues in panic disorder [21,33], somatoform disorder [34,35], dissociative disorders [36][37][38] or eating disorders [39,40]. Maladaptive stress reactivity in terms of cognitive and emotional response to issues in processing interoceptive information may contribute to poor somatic health [41].…”
Section: Introductionmentioning
confidence: 99%